Pengembangan Mesin Pengiris Pisang Inovatif pada Usaha Olahan Pisang Cesy Lia - Lina Maulidiana; Defrizal Defrizal; Martinus Martinus; Arnofdwi Ferdiza; Hikmal Yusuf (Universitas Malikussaleh, 2026)
Community Service activities for Cesy Lia banana chip MSMEs are carried out through the Development of an Innovative Banana Slicing Machine. Cesy banana chip MSMEs have high economic potential due to abundant raw materials, relatively simple production technology, and stable market demand. However, the